(untitled) (Research, Society and Development, 2021)
During the COVID-19 pandemic, infection by the SARS-CoV-2 virus, which causes severe respiratory syndrome. Unlike other viral infections, its response to inflammation diverges from the usual, thus becoming an enigma to understand the cellular function during the immune response. Thus, many studies have started to elucidate the main cells, TCD4, TCD8, B lymphocytes and antibodies. This review aims to search in articles and scientific research related to the subject, via databases such as Google Scholar, Elsevier, PubMed, Medline, The New England Journal of Medicine and Scielo, texts related to the general characteristics of COVID-19 and the immunology related to infection by the SARS-CoV-2 virus. Although more studies are needed, a picture has begun to emerge that reveals that TCD4 + cells, TCD8 + cells and neutralizing antibodies, contribute to the control of SARS-CoV-2 in both non-hospitalized and hospitalized cases of COVID-19. The specific functions and kinetics of these adaptive immune responses are discussed, as well as their interaction with innate immunity and implications for COVID-19 vaccines and immunological memory against reinfection. Thus, we emphasize the importance of maintaining the care related to hygiene and protection, following the recommendations of world health agencies.